A novel dual‐decomposition method for non‐convex two‐stage stochastic mixed‐integer quadratically constrained quadratic problems - Belyak, Nikita; Oliveira, Fabricio (International transactions in operational research, 2025)
We propose the novel p ‐branch‐and‐bound method for solving two‐stage stochastic programming problems whose deterministic equivalents are represented by non‐convex mixed‐integer quadratically constrained quadratic programming (MIQCQP) models. The precision of the solution generated by the p ‐branch‐and‐bound method can be arbitrarily adjusted by altering the value of the precision factor p . The proposed method combines two key techniques. The first one, named p ‐Lagrangian decomposition, generates a mixed‐integer relaxation of a dual problem with a separable structure for a primal non‐convex MIQCQP problem. The second one is a version of the classical dual decomposition approach that is applied to solve the Lagrangian dual problem and ensures that integrality and non‐anticipativity conditions are met once the optimal solution is obtained. This paper also presents a comparative analysis of the p ‐branch‐and‐bound method efficiency considering two alternative solution methods for the dual problems as a subroutine. These are the proximal bundle method and Frank–Wolfe progressive hedging. The latter algorithm relies on the interpolation of linearisation steps similar to those taken in the Frank–Wolfe method as an inner loop in the classic progressive hedging. The p ‐branch‐and‐bound method's efficiency was tested on randomly generated instances and demonstrated superior performance over commercial solver Gurobi.